2020
DOI: 10.1007/s10792-019-01250-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 27-gauge versus 25-gauge vitrectomy results in patients with epiretinal membrane: 6-month follow-up

Abstract: Purpose To compare the 27G versus 25G vitrectomy in patients with epiretinal membrane (ERM). Patients and methods Sixty pseudophakic eyes of 60 consecutive patients treated by pars plana vitrectomy (PPV) using 27G (30 eyes) or 25G (30 eyes) were prospectively evaluated including eye's inflammation, surgery time, ERM ? ILM removal time and complications. Additionally, 1, 3, 7, 14, 30, 90 and 180 days after PPV, the following were estimated: intraocular pressure (IOP), sclerotomy wound closure time, distance bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 21 publications
4
25
1
2
Order By: Relevance
“…The significantly shorter mean surgical time demonstrated with 27G instrumentation for both ERM and FTMH is encouraging and could be partially attributed to the greater functionality associated with the 27G system versus the 25G system or the surgeon's greater ease at achieving wound closure after trocar removal with a smaller gauge. However, this does appear to contradict other studies that have generally demonstrated a small increase in surgical time with the 27G system [4,19,22].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The significantly shorter mean surgical time demonstrated with 27G instrumentation for both ERM and FTMH is encouraging and could be partially attributed to the greater functionality associated with the 27G system versus the 25G system or the surgeon's greater ease at achieving wound closure after trocar removal with a smaller gauge. However, this does appear to contradict other studies that have generally demonstrated a small increase in surgical time with the 27G system [4,19,22].…”
Section: Discussioncontrasting
confidence: 59%
“…Micro-Incision Vitrectomy Surgery (MIVS) offers an excellent safety profile for patients, while the newest 27-gauge (27G) systems have potential additional safety and outcome benefits when compared to earlier MIVS platforms. This innovation towards progressively smaller instrumentation is playing a major role in the evolution of posterior segment surgery by allowing for decreased incision size and, possibly, less pain, [1,2] fewer post-surgical wound leaks and subsequently, faster recovery times [3][4][5] with a low risk of other post-operative complications (6)(7)(8). Specifically, multiple large cohort studies and a 2013 literature review concluded there was no increased risk of endophthalmitis when comparing MIVS to 20-gauge (20G) vitrectomy [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Significant heterogeneity was found ( I 2 = 92%), so random effects were used. The study of Lubinski et al [ 24 ] was the main contributor of heterogeneity, and after reevaluating this study, we found nothing wrong ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 47%
“…Seven studies [ 15 , 21 24 , 26 , 31 ] were designed as prospective randomized/nonrandomized comparative study and four studies [ 17 , 25 , 29 , 30 ] were retrospective randomized/nonrandomized comparative study. Five trials [ 15 , 17 , 21 , 24 , 29 ] enrolled 554 eyes which were conducted on ERM and six studies [ 22 , 23 , 25 , 26 , 30 , 31 ] enrolled 386 eyes which were conducted on RRD. In total, 940 eyes were included in this meta-analysis; 439 eyes were assigned to the 27-G vitrectomy group and 501 eyes to the 25-G group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation